Pengaruh Penambahan Buah Nangka Muda terhadap Sifat Fisik dan Organoleptik Abon Daging Itik Afkir - Rasman, Rasman; Hafid, Harapin; Nuraini, Nuraini (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2018)
This study was conducted to determine the physical characteristics and organoleptic qualities of spent duck abon with the addition of unripe jackfruit. The materials used were spent duck meat, unripe jackfruit, garlic, shallot, candlenut, coriander, coconut, brown sugar, salt, water, and cooking oil. The design used in this study is completely randomized design consisted of 4 treatment (A0: 100% duck meat, A1: 85% duck meat and 15% unripe jackfruit, A2: 70% duck meat and 30% unripe jackfruit, A3: 55% duck meat and 45% unripe jackfruit) with 3 repetition for physical variables, and 15 panelists for organoleptic test. The results of this study suggested that addition of unripe jackfruit in spent duck abon showed no significant difference for pH and rendemen. Organoleptic qualities (aroma, color, flavor and texture) of spent duck abon showed no significant difference with unripe jackfruit aditition.Keywords: abon, spent duck meat, unripe jackfruit, physical characteristic, organoleptic qualities